If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + -30x + -16 = 0 Reorder the terms: -16 + 25x + -30x = 0 Combine like terms: 25x + -30x = -5x -16 + -5x = 0 Solving -16 + -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -5x = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -5x = 0 + 16 -5x = 0 + 16 Combine like terms: 0 + 16 = 16 -5x = 16 Divide each side by '-5'. x = -3.2 Simplifying x = -3.2
| -16-9-2= | | 4(x+15)=17x | | -4y+8=5y+9 | | -4(-2+5)= | | 5t^2+14x+3=0 | | 6y+8y=98 | | 15+2(9-6)+9= | | 5x-y+15=0 | | 15+2(9-6)-9= | | x-15=-4 | | -18+12+-6= | | -9(3b+1)+(28b-9)=0 | | (-18)(12)(-6)= | | 5p-6(p-5)+5(q-5)= | | 3(-6)(4)(-2)= | | (6u^3)(-5u^7v^6)= | | 3(-6)(4)(-2)=(-18)(12)(-6) | | 18=6x | | 9y-7(x-y)-x= | | N^2-3+2=0 | | 13x+6-3=12x-3 | | 4(9b+c-5a)-5(a-3c+4b)= | | 33=(3x-8)(7x+4) | | 7(p+7q-13)= | | N^2-13n+40=0 | | 5(6y+12)=6(12y-4) | | 30=-1.2v | | 2x^2+10x-18=0 | | 5(6y+12)=6(12-4) | | -2(4n+4)=2 | | 15x^4-12x^3+3x^2=0 | | y-(-3)=2(x-2) |